2016
DOI: 10.1016/j.ijcha.2016.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of quantitative echocardiographic measures of right ventricular function as compared to cardiovascular magnetic resonance

Abstract: BackgroundMany echocardiographic parameters have been proposed to evaluate right ventricular (RV) systolic function. We comprehensively assessed a wide range of quantitative echocardiographic parameters in a single cohort compared with same-day cardiovascular magnetic resonance (CMR).Methods and results92 subjects were examined prospectively: Group 1 consisted of 46 healthy controls (21 males, 33.4 ± 11.4 years), Group 2 consisted of 46 patients (20 males, 38.5 ± 18.9 years) undergoing RV functional assessment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 24 publications
0
25
0
1
Order By: Relevance
“…RVMPI values of >0.4 and <0.25 were predictive of RVEF<35%, and ≥50%, respectively (44). In addition to RVMPI, myocardial tissue velocities (Sa, Ea, Aa, Ea/Aa, E/Ea), TAPSE (Tricuspid annular plane systolic excursion), and 3DE-RV findings were proportional to using CMR reference ranges (8,23,45,46).…”
Section: Comparison Of Rvmpi With Cardiac Mri (Cmr) Findingsmentioning
confidence: 95%
See 1 more Smart Citation
“…RVMPI values of >0.4 and <0.25 were predictive of RVEF<35%, and ≥50%, respectively (44). In addition to RVMPI, myocardial tissue velocities (Sa, Ea, Aa, Ea/Aa, E/Ea), TAPSE (Tricuspid annular plane systolic excursion), and 3DE-RV findings were proportional to using CMR reference ranges (8,23,45,46).…”
Section: Comparison Of Rvmpi With Cardiac Mri (Cmr) Findingsmentioning
confidence: 95%
“…Cardiac Magnetic Resonance (CMR) imaging is widely used in the assessment of cardiac function. It is the gold standard method in the assessment of RV function in rTOF patients (8,9). However, it is expensive and time-consuming compared to the echocardiographic methods.…”
Section: Contextmentioning
confidence: 99%
“…Current echocardiographic guidelines recommend combining various echocardiographic parameters to assess RV function [21]. Clinically used parameters include the fractional area change (FAC), which is a surrogate of ejection fraction and correlates with RV ejection fraction estimated by cardiac magnetic resonance better than other parameters [19,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Published studies have shown good to excellent correlation between LVEF and RVEF measured in 3D-ECHO and CMR with a documented tendency towards minimal (although statistically significant) underestimation of 3D-ECHO results [23,24]. Most of those studies concerned adults [25][26][27][28][29]. The literature comparing results of 3D-ECHO and CMR in children is much scarcer both in number and resources [27].…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, systematic, regular, and accurate assessment of ventricular function in children with arrhythmia, even (or maybe especially) idiopathic, is crucial. 3D-ECHO appears to be the perfect tool for this purpose and a valuable alternative to CMR in this population [26][27][28][33][34][35][36].…”
Section: Discussionmentioning
confidence: 99%